2010
DOI: 10.1097/mrr.0b013e328335213f
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific chronic low back pain patients are deconditioned and have an increased body fat percentage

Abstract: The aim of this cross-sectional study was to compare data on the level of aerobic capacity and body composition of nonspecific chronic low back pain (CLBP) patients with normative data matched for sex, age and level of sporting activity. The study population consisted of 101 outpatients with nonspecific CLBP who had entered a rehabilitation programme. Results were as follows: the mean (standard deviation) aerobic capacity (VO2max) of CLBP patients was significantly (P<0.001) lower 7.3 (5.6) ml/kg lean body mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 21 publications
(20 reference statements)
0
22
0
Order By: Relevance
“…Individuals with CLBP often have an increased body fat percentage and body mass index (BMI), which may modulate pain through peripheral sensitization from increased systemic inflammation . Furthermore, increased fat infiltration of paraspinal musculature (particularly the lumbar multifidus) has been observed in CLBP, and could be associated with an increased BMI .…”
Section: Multidimensional Assessment Of Chronic Low Back Painmentioning
confidence: 99%
“…Individuals with CLBP often have an increased body fat percentage and body mass index (BMI), which may modulate pain through peripheral sensitization from increased systemic inflammation . Furthermore, increased fat infiltration of paraspinal musculature (particularly the lumbar multifidus) has been observed in CLBP, and could be associated with an increased BMI .…”
Section: Multidimensional Assessment Of Chronic Low Back Painmentioning
confidence: 99%
“…The test has been referred to as a reliable, valid, and feasible instrument for calculating VO2 max in patients with nonspecific low back pain 23 and stroke.…”
Section: Laboratory-based Testsmentioning
confidence: 99%
“…16,23,43 Thus, physiotherapists treating patients with MSCs in outpatient clinics should include an individually tailored exercise program in the treatment plan for these patients. For optimal health benefits, it is important that exercise programs are in accordance with current recommendations.…”
mentioning
confidence: 99%
“…In addition, it has been shown that individuals with chronic LBP have reduced physical fitness levels compared with healthy asymptomatic subjects [24]. Moreover, it has been stated that chronic LBP sufferers have lower aerobic capacity and a higher fat percentage than their healthy controls [25]. It should be pointed out, however, that these findings mainly originate from a cross-sectional study setting, and thus may be biased.…”
Section: Introductionmentioning
confidence: 99%